Distribution of flying insects across landscapes with intensive agriculture in temperate areas. (October 2021) - Musters, C.J.M.; Evans, Tracy R.; Wiggers, J.M.R.; van 't-Zelfde, Maarten; de Snoo, Geert R.
Highlights: Flying insects were caught with sticky traps on fields in Illinois and The Netherlands. No effect of distance to (semi)natural area was found on the abundance of insects. We did find an effect of landscape, vegetation height and plot location. Flying insects are highly mobile, so abundance may be homogenized over large areas. The effect of nature conservation on flying insects should be studied on large scales. Abstract: The abundance of insects has been strongly decreasing over the last decades, at least in the temperate zones of North America and Europe. This decrease has generally been attributed to increased human activity, especially increased agricultural production. Therefore, one would expect that insect abundance is spatially distributed according to human land use, more specifically that the abundance of insects in agricultural fields should be affected by the distance to (semi)natural areas. We tested this expectation on an extensive dataset of flying insects from Illinois, USA, and the Netherlands, Europe. Flying insects were collected with yellow sticky boards in agricultural fields at distances up to 566 m from (semi)natural areas. We did not find any effect of distance to (semi)natural area on the abundance of flying insects, after correcting for the confounding variables 'landscape complexity', 'vegetation height' and 'plot locations' (interior vs edge of the field). One might prematurely infer from this that (semi)natural areas do not affect flying insect abundance. We argue that knowing that flying insects are highly mobile, both active and passive, although sticky boards sample local insect abundance, abundance may be homogenized over a relatively large area in open landscapes. Therefore, the study of the effect of nature conservation management on flying insects should be done on spatially large scales, e.g., the landscape level.